Hydration strategies of professional elite rugby league referees during super league matches. Issue 1 (February 2016) - Jones, Ben; Till, Kevin; Emmonds, Stacey; King, Roderick FGJ; Gray, Michael P; Beggs, Clive B; O'Hara, John P
Due to the focus of research within athletic populations, little is known about the hydration strategies of rugby league referees. We observed all eight full-time professional referees, during 31 Super League matches to investigate the drinking strategies and magnitude of dehydration (body mass loss) experienced by referees during match play. Referees arrived and remained euhydrated (urine osmolality; pre and post-match 558 ± 310 and 466 ± 283 mOsmol·kg −1 ). Mean body mass change was −0.7 ± 0.8%, fluid loss was 890 ± 435 g and fluid intake was 444 ± 167, 438 ± 190, 254 ± 108 and 471 ± 221 g during pre-match, first half, half-time and second half. This study suggests that elite referees adopt appropriate hydration strategies during match-play to prevent large reductions in body mass, although individual variability was observed. Future research should investigate dehydration in referees from other sports and the effects on refereeing performance.